Foot Massage terhadap Tekanan Darah Penderita Hipertensi - Yulianti, Yeni; Tresnawan, Teten; Asmarawanti, Asmarawanti; Susilawati, Susilawati; Mustaqimah, Yurisma Khoerul (Journal of Telenursing (JOTING), 2023)
This study aims to identify differences in the mean value of systolic and diastolic blood pressure reduction in hypertension sufferers in the intervention and control groups. The method used is Quasi Experiment pre-test and post-test with a control group design. This study showed a significant difference in the mean values of systolic and diastolic pressure before and after foot massage for 30 minutes, carried out three times within six days in the intervention group. Hypothesis testing was carried out using the Independent Samples Test statistical test, obtaining a p-value of 0.000. In conclusion, there is a significant difference in systolic and diastolic blood pressure between the intervention group and the control group Keywords: Diastolic, Foot massage, Hypertension, Systolic